الأنساق المضمرة في قصيدة وطاوي ثلاث "الكرم" للحطيئة - محيي الدين، وائل عبدالله حسين (جامعة الإسراء, 2024)
تتناول هذه الدراسة الأنساق المضمرة في قصيدة (الكرم) المنسوبة للشاعر الحطيئة، بعيدًا عن الجماليات البلاغية التي شكلت عبر ردح من الزمن واجهة خداعةً، استطاع الحطيئة من خلالها استعمال البلاغة قناعا أخفى خلفه كثيرًا من (المعاني المتوارية). وبالقدر الذي زخرت به تلك القصيدة من جمالياتٍ بلاغية فإنها تُضمر أنساقا ثقافية وقبحيات تنقض هذه الجماليات، وقد اعتمدت الدراسة المنهج التاريخي سبيلا لاستنطاق ما توارى من قبح خلف ذلك الجمال المعلن، ما يشي بأن الشاعر قد توسل ما هو جمال ظاهر؛ ليُمرّر ما انطوى عليه نصه من معان اجتماعية مضمرة. This study investigates the implicit patterns in Al-Karam (generosity) Poem attributed to the poet Al- Hutay’ah. Regardless of the rhetorical aesthetics that formed over a long period of time in Arabic poetry a deceptive façade, Al- Hutay’ah was able to use rhetoric as a mask behind which he hid a myriad of hideous ideas and images. While this poem is rich in rhetorical aesthetics, it indeed implicitly contains cultural and literary patterns as well as ugliness that contradict these aesthetics. The study uses the cultural method as a means to unravel and assess the latent hideous ideas and images covered by the aesthetic features and beauty of the poem. Thus, it alludes that the poet utilized what is apparent beauty to pass the latent ugliness contained in the text.
Keywords: القصائد الشعرية -- الجماليات البلاغية -- الأنساق الثقافية -- قصيدة وطاوي ثلاث -- الحطيئة، جرول بن أوس، ت. 674 م